Lingkungan Kerja, Budaya Organisasi Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Tendik Fakultas Kedokteran UNS - Moch. Zaeny Ari Sucipto; Sudarwati; Istiatin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of work environment, organizational culture, and leadership style on the performance of educational staff (TENDIK) at the Faculty of Medicine, Universitas Sebelas Maret. These three variables were examined because they play an essential role in improving work effectiveness and supporting institutional goals. A quantitative research method was employed by distributing questionnaires to 92 respondents from a population of 120 staff members. The research instrument used a Likert scale and was tested through validity and reliability assessments. Data were analyzed using multiple linear regression with SPSS to measure the influence of each independent variable on the dependent variable. The results indicate that work environment, organizational culture, and leadership style positively and significantly affect staff performance. Simultaneously, the three variables contribute 63.9% to performance variation, while the remaining 36.1% is influenced by other factors outside this study. These findings emphasize that improving staff performance can be achieved through enhancing workplace conditions, strengthening organizational culture, and applying effective leadership styles.